Vieillir vert et digitalisé : connaissances et habitudes pro-environnementales de Belges de plus de 60 ans dans une société digitalisée - Rosie Harrington; Louise-Amélie Cougnon; Andrea Catellani; Armelle Nugier (VertigO, 2023)
The role of human activity in climate change (CC) has generated a particular enthusiasm for research, all research fields combined: these studies focus on people's perceptions and their motivation to contribute, individually or in groups, to reducing these changes. Other studies have aimed to shape communication campaigns so that they succeed in involving individuals in the fight against CC. Some of these studies have examined the links between beliefs, media use and pro-environmental habits; however, few of them have focused specifically on older people. The aim of this study is therefore to explore the links between beliefs, media use and pro-environmental habits in a sample of people aged over 60 (N = 305). The main results of this correlational study suggest that the participants in our sample consider themselves to be well informed about CC and are less disconnected from the internet and computer tools than in other older studies and use Facebook more than any other social network. Furthermore, their beliefs about CC are significantly correlated with their pro-environmental habits, and these habits do seem to be linked to their use of certain information and communication technologies. The overall results of this study, their implications and limits are reviewed in the paper's discussion section.